APLIKASI METODE FUZZY TSUKAMOTO DALAM SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN JUMLAH PERSEDIAAN BERAS PADA PERUM BULOG DIVRE SUMUT - MEILIYANI BR GINTING; YUYUN DINASARI ARITONANG; RAHELIYA BR GINTING (JURNAL ILMIAH SIMANTEK, 2020)
Indonesia's food security development, which guarantees the availability and consumption of adequate food, safe, quality,and nutritious balance at the household, regional, and national levels throughout the time and evenly. The food supply thatcan be accessed by any household at affordable prices is very important for the creation of food security, and the economicdevelopment of Indonesia. Many methods are used to deal with uncertainty in determining the rice supply. One is to usefuzzy logic. The fuzzy logic is a logic that confronts the concept of a partial truth, where the classical logic states thateverything can be expressed in binary terms (0 or 1).